Green space quantity and exposure in relation to the risk of immune-mediated diseases: a scoping review - Galitskaya, Polina; Luukkonen, Anna; Roslund, Marja I.; Mänttäri, Miia; Yli-Viikari, Anja; Tyrväinen, Liisa; Sinkkonen, Aki; Laitinen, Olli (Springer Science and Business Media LLC, 2024)
The growing global incidence of immune-mediated and inflammatory diseases (IMIDs) is worrisome, with evidence suggesting that environmental factors, notably urbanization and the reduction of green spaces, may act as potential instigators. However, conflicting findings in studies necessitate a closer examination of recent research (January 2020 – February 2024) to elucidate the factors contributing to these inconsistencies. This review explores study protocols to avoid erroneously endorsing the null hypothesis of no association between green space coverage and IMID risks. A literature search adhering to PRISMA-ScR guidelines yielded 46 relevant papers from Google Scolar and Pub Meb. The studies varied in design, with 17 being longitudinal, 24 cross-sectional, and five focusing on longitudinal parent-offspring connections. Geographic scope differed, with 21 multi-location and 25 single-location studies. Participant numbers ranged from 144 to 982,131 across diverse demographics. Additionally, some studies examined disease frequencies in large groups (several million people) residing in specific regions. Green space metrics encompassed NDVI, land cover data, plant biodiversity, and novel indexes, measured within 7.5–5000 m diameter buffers around residences or schools. The review advises against making definitive statements regarding the relationship between urban green spaces and the prevalence of IMIDs. It suggests that inconsistencies in study results may stem from variations in study designs and methodologies, as well as the complex, interacting mechanisms through which green spaces affect immune health. Future research recommendations include larger cohorts, early-life exposure data, and testing specific hypotheses related to vegetation types and participants’ genetic predispositions.
Keywords: immunemediated and infammatory diseases; green area; green space; green cover; biodiversity hypothesis; NDVI; land use and land cover